SIFAT FISIK TANAH YANG MEMENGARUHI KEJADIAN LONGSOR DI MAKALE SELATAN: The Physical Properties of Soil that Affected the Landslide Event in South Makale - Patandung, Tania; Ahmad, Asmita; Rismaneswati (Jurnal Ecosolum, 2020)
The soil susceptibility increases in line with decreased soil stability and the ability of soil to pass water which, affected by the soil's physical characteristics. The research aims to analyze the physical properties of soil that affected landslide events in South Makale. This research using the method of comparative analysis by comparing the soil characteristic in the landslide and non-landslide areas. The soil has 6 class textures namely silt loam, loam, clay loam, silty clay loam, silty clay, and sandy clay loam. Soil Permeability ranges 0.22-6.98 cm/h (slowly-rather quickly). On the non-landslide areas, soil permeability is relatively low with values of 0.55 to 0.72cm/hour. The soil liquid limit value on the landslide area reached the value max of 67.7%, with the plasticity index value max 21.77%. The liquid limit in the non-landslide area reached a value max of 45.0% with a plasticity index value max 8.56%. Soil with silt and clay fraction dominant have a relationship with the landslide event. Soil with the silt and clay fraction dominant causes a decrease in the permeability value and affects the increase in liquid limit value and soil plasticity index.